Pengaruh Penggunaan Media Sosial Tiktok Terhadap Perilaku Konsumtif Siswa Muslim Sekolah Menengah Atas Negeri 4 Medan - Muhammad Riannur Hidayah Sitepu (Sekolah Tinggi Agama Islam As-Sunnah, 2025)
This study aims to answer whether there is an influence of TikTok social media on the consumptive behavior of Muslim students at SMA Negeri 4 Medan. This research employs a quantitative approach with correlation methods. The population consists of all Muslim students in grade X at SMA Negeri 4 Medan, with a sample of 70 respondents selected through random sampling. The research instrument used is a Likert-scale questionnaire. Research data was processed and analyzed using the Product Moment correlation method. To facilitate the process, SPSS version 29 for windows was used. The findings reveal a significant influence of TikTok on consumptive behavior, with a correlation coefficient of 0.331, significant at 0.005 (<0.05). TikTok contributes 10.9% to consumptive behavior, while other factors account for the remaining percentage.